The effect of silver nanoparticles and silver ions on zebrafish embryos (Danio rerio) - Caloudova, Hana; Hodkovicova, Nikola; Sehonova, Pavla; Blahova, Jana; Marsalek, Blahoslav; Panacek, Ales; Svobodova, Zdenka (Neuro endocrinology letters, 2018)
OBJECTIVES: The aim of this study was to establish and evaluate the mortality rate, hatching rate and observe the presence of sublethal changes in zebrafish embryos after exposure to silver ions and nanoparticles. METHODS: Tests were conducted on newly fertilized zebrafish embryos, according to the modified OECD guideline 236, using a semistatic method and 96 hour incubation time. Silver nitrate and two different silver nanoparticles, stabilized with 0.01% solution of maltose and gelatine in the first case, and stabilized with polyvinylpyrrolidone, in the latter, were tested. RESULTS: Significant differences in toxicity of tested substances were recorded. The value of 96hLC50 for silver nitrate was 58.44 μg/L. The value of 96hLC50, calculated for silver nanoparticles stabilized with 0.01% solution of maltose and gelatine, was nearly 100 times higher, 4.31 mg/L. The value 96hLC50 for silver nanoparticles stabilized with polyvinylpyrrolidone exceeded 100mg/L, occurrence of sublethal effects caused by silver nanoparticles stabilized with polyvinylpyrrolidone was insignificant in most of the exposition groups, but only in this substance caused decreased hatching rate. CONCLUSION: Properties of different silver nanoparticles play an important role in levels of their toxicity and predominant mechanisms of action. In general, silver nanoparticles are less toxic for Danio rerio embryos than silver ions.
Keywords: Embryo, Nonmammalian; Zebrafish; Silver Nitrate; želatina; Silver; LD50; Nanoparticles; nanočástice; dusičnan stříbrný; dánio pruhované; Maltose; Animals; Povidone; zvířata; povidon; Lethal Dose 50; stříbro; maltosa; embryo nesavčí; Gelatin